Relationship of the frequency scale for symptoms of gastroesophageal reflux disease with endoscopic findings of cardiac sphincter morphology - Tsuboi, Kazuto; Omura, Nobuo; Yano, Fumiaki; Kashiwagi, Hideyuki; Yanaga, Katsuhiko (Journal of gastroenterology, 2008)
Background Kusano et al. developed a questionnaire for the evaluation of gastroesophageal reflux disease (GERD), the frequency scale for the symptoms of GERD (FSSG). The FSSG is now widely used in Japan. We investigated the relationship between FSSG results and cardiac sphincter endoscopic findings. Methods The subjects were 470 patients who responded to the FSSG before undergoing endoscopy. From the FSSG results, we calculated the total, acid reflux, and dysmotility scores. Endoscopic findings were assessed in terms of the anatomic-functional-pathological (AFP) classification as the A factor, or degree and type of hiatal hernia, and the valve factor, or laxity of the cardiac sphincter. The degree of esophagitis was assessed using the modified Los Angeles classification. We investigated correlations between each score and the anatomy of the cardia. Results With either definition of esophagitis (grade M or greater, or grade A or greater), the total and acid reflux scores were both significantly higher in the group with reflux esophagitis than in the group without reflux esophagitis. Examination of the relationship between FSSG scores and the A factor revealed no significant differences in the total, acid reflux, or dysmotility scores whether a hiatal hernia was present or absent. Similarly, examination of the valve factor showed no significant difference in any scores between V0 and V1 versus V1 and V2, indicating no correlation between cardiac sphincter laxity and FSSG scores. Conclusions The FSSG was useful in determining whether reflux esophagitis is present, but it did not predict the anatomy of the cardia.